Pronunciation Error Analysis of English Schwa Sound Produced by the Students of UNSIQ - Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2019)
This article presents the study result of error analysis on English sounds pronunciation produced by Indonesian students studying at Faculty of Language and Literature of Universitas Sains Al-Qur’an (UNSIQ). Students had many problems related to adapt English sound system as they learnt English in the class. The Focus of this study is to analyze the pronunciation errors of English vowel sound namely ‘schwa’ which is symbolized as /ə/ in phonetic writing based on IPA (International Phonetic Association). This study applies qualitative research methodology. In collecting the data, the researcher attempted to arrange and compile schwa sound utterances in a text and give the text to be read by students. Through the step of listening and recording the students’ pronunciation, the researcher eventually got the data source to be analyzed. The methods of analyzing the collected data, among others are, listening to the student’s pronunciation, making notes of pronunciation errors made by students, and analyzing the problems of mispronunciation of English schwa produced by students. The result of the study shows that English schwa sounds produced by the students are affected by the student’s habit of speaking in their colloquial language of their mother tongue. Even though in Indonesian language they have such a schwa sound, however, it does not mean that they alert with correct pronunciation as they were examined to read the given utterances in correlation with pronouncing test of English schwa sound. Keywords: English schwa, phonology, pronunciation errors